SAKLAR SUARA MENGGUNAKAN ARDUINO BERBASIS ANDROID - Rusli H; Sulaeman; Juniarti Iryani; muhammad awal nur (Jurnal Sistem Informasi dan Komputer (JSIKOM), 2021)
The research aims to: (1) produce a tool that can control the lighting of the lights at home using Android through human voice. (2) Implement a sound switch using an Android-basedArduino.The research method we use in making sound switch tool using Android-based Arduino is Action research method (Action Research) that attempts to try to get ideas into Prektik to fix or change something for real impact. As for Action research measures (Action Research): (1) plan; (2) Action; (3) Observation; (4) reflection;. The Technical data collection (1) observation; (2) interviews; (3) Library study.The results showed that (1) This tool can be turned on/off when user gives command via Android "turn on lamp/delete lamp"; (2) The sound switch using this Android-based Arduino uses the Arduino as a brain that will process the input data of the android connected through the Bluetooth module HC 05; (3) This tool is made to provide ease for people who are sick or have a physical defect to turn on and extinguish the lights remotely using Android.